Arrangement and Implementation of Fulfillment of Health Guarantee Rights for Persons with Disabilities in the Special Region of Yogyakarta - Ramadhani, Milenia; Hartanto, Hartanto; Rusdi, Muhamad (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human Rights (HAM) are rights given to humans simply because they are human. Not because of positive law, but because of their human dignity; So the great attention to people with disabilities, which is carried out by the DIY government, is motivated by awareness of human rights, for people with disabilities who are included in vulnerable groups. The number of people with disabilities in the Special Region of Yogyakarta (DIY) is also quite large, so this research will analyze how the regulation and implementation of fulfilling the right to health insurance for people with disabilities in DIY is regulated.The push to formulate regional level regulations for people with disabilities was carried out by the central government, the DIY regional government and disability advocates or activists as well as people with disabilities. DIY has 4 districts and 1 city, each of which has a disability regional regulation in order to fulfill the regulations for implementing health services for people with disabilities in their respective regions according to their potential. However, existing regional regulations must not conflict with higher regulations, including the DIY Regional Regulation. The implementation of these arrangements means that activities are carried out well. This can be seen from the efforts made by DIY in collaboration with City Districts in health programs and funding for people with disabilities, including assistance with assistive devices. Although obstacles are still encountered, in general it can be said to be going well. Improvement prioritizes valid data collection, coordination between stakeholders and simplifying requirements for people with disabilities who want to fulfill their rights in the health sector.